Impact of Micro Finance: Exploring the Link between Microfinance and Poverty in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
An estimated of about 300 millions in India and around1.2 billion population worldwide live in absolute poverty. They are unable tomeet their most basic human needs for food, clothing, shelter and minimumhealth care. Since 1947, the absolute number of poor has doubled despite thesignificant growth in agriculture production and employment over the past fivedecades of development planning. Rural poverty continues to pose the greatestchallenge in India. India today retains the dubious distinction of having thelargest number of poor people on the planet. Poverty in India is closelyassociated with poor population, or an imbalance between population and landresources. In India landless or near landless people live close to the marginof existence experiencing seasonal unemployment and nutritional stress. Theburden of such poverty falls heavily upon women and children. The low level ofhuman development is both a cause and consequence of poverty.